If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5v + 9 = 33 Reorder the terms: 9 + 5v = 33 Solving 9 + 5v = 33 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 5v = 33 + -9 Combine like terms: 9 + -9 = 0 0 + 5v = 33 + -9 5v = 33 + -9 Combine like terms: 33 + -9 = 24 5v = 24 Divide each side by '5'. v = 4.8 Simplifying v = 4.8
| 42/7a | | (4x+1)(7x-6)=0 | | 5x^2-7+2=0 | | 9x+1=3x+31 | | (2x+4)*(x-1)-36=0 | | 180x^4-108x^3-107x^2+36x+20=0sol | | 4x=46-10 | | 3(2x+1)+5=7-3x | | 9x-7=-2x+-40 | | 4/5c•4c/18 | | 7x-8=9x+(2) | | Ln(2.5x)=3 | | 13x-66=90 | | 3x+5y-7x=37findx | | y^2+2y+x^2-24=14 | | 9x+2=7x+-14 | | 10x-20=7x+10 | | 6x+56+10=180 | | 0.9/COS | | 5(3x+5)=4(3x+4)+3 | | -5(5-x)+4=3(x-1) | | (-2x)/(12x) | | 2(3x+5)=4(x-5)+2x | | -2x/12x | | 6x+3=-3x+-60 | | 4(2x-2)=3(5x-3) | | -2b+8=-15 | | -198=-18x | | 6(x-4)=3(2x-5) | | 4(3-x)-(12+x)=4 | | p+1=11 | | -6(1)+2= |